Can Service Be a Growth Escalator in Low Income Countries? - Ghani, Ejaz (World Bank Group, Washington, DC, 2014)
Several high-level reports have raised the concern that low-income countries, especially in Africa, are experiencing premature de-industrialization. The concern is that they are growing without transforming. Have the latecomers to development missed the boat? Although these concerns are well placed, Africa's growth seems to be benefitting from a structural transformation of a different kind. The manufacturing sector as a share of gross domestic product has shrunk, but countries have benefitted from the third industrial revolution with globalization of services being at the forefront of this technological revolution. As services produced and traded across the world expand with globalization, the possibilities for low-income countries to develop based on their comparative advantage expand. That comparative advantage can just as easily be in services as in manufacturing. Comparative advantage need not be a one-trick pony.